2020
DOI: 10.7554/elife.53999
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium leak lowers glucose storage in human muscle, promoting hyperglycemia and diabetes

Abstract: Most glucose is processed in muscle, for energy or glycogen stores. Malignant Hyperthermia Susceptibility (MHS) exemplifies muscle conditions that increase [Ca2+]cytosol. 42% of MHS patients have hyperglycemia. We show that phosphorylated glycogen phosphorylase (GPa), glycogen synthase (GSa) – respectively activated and inactivated by phosphorylation – and their Ca2+-dependent kinase (PhK), are elevated in microsomal extracts from MHS patients’ muscle. Glycogen and glucose transporter GLUT4 are decreased. [Ca2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(51 citation statements)
references
References 81 publications
6
44
0
1
Order By: Relevance
“…7 The authors found significant changes in the metabolites of various pathways involved in carbohydrate and lipid metabolism between MHS and MHN patients, with an overall shift in energy production from carbohydrate to lipid substrates. Alterations in carbohydrate utilization is consistent with the results of studies using muscle samples from human MHS patients and mouse models of MH, 8,9 as well as showing an impaired aerobic metabolism that would be expected with such a shift in energy substrate. 8,10 -12 Interestingly, these authors found that the shift to lipid metabolism appeared to be imperfect with an accumulation of fatty acids.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…7 The authors found significant changes in the metabolites of various pathways involved in carbohydrate and lipid metabolism between MHS and MHN patients, with an overall shift in energy production from carbohydrate to lipid substrates. Alterations in carbohydrate utilization is consistent with the results of studies using muscle samples from human MHS patients and mouse models of MH, 8,9 as well as showing an impaired aerobic metabolism that would be expected with such a shift in energy substrate. 8,10 -12 Interestingly, these authors found that the shift to lipid metabolism appeared to be imperfect with an accumulation of fatty acids.…”
supporting
confidence: 87%
“…7 Les auteurs ont observé d'importants changements dans les métabolites de diverses voies impliquées dans le métabolisme des glucides et des lipides entre les patients SHM et NSHM, avec une transition globale de la production énergétique des glucides aux substrats lipidiques. Les modifications dans l'utilisation des glucides concordent avec les résultats d'études utilisant des échantillons de muscles de patients humains SHM et de modèles murins d'HM, 8,9 en plus de montrer une altération du métabolisme aérobie en accord avec un tel changement dans le substrat énergétique. 8,10 - 12 Il est intéressant de relever que ces auteurs ont constaté que le passage à un métabolisme lipidique semblait imparfait, avec une accumulation d'acides gras.…”
unclassified
“…This conclusion is substantiated by the converse observation that insulin-stimulated glycogen synthesis is normal in mice expressing a knockin mutation in GSK3 that impairs its phosphorylation and hence prevents inhibition of its activity toward GS (Bouskila et al, 2008). Finally, superimposed on the activity levels of the enzymes involved in glycogen synthesis is their subcellular localization and their regulation by cytosolic Ca 2+ (Tammineni et al, 2020).…”
Section: Insulin Signaling Toward Glycogen Synthesismentioning
confidence: 91%
“…To provide an explanation for the extraordinary fast activation of pSOCE (Launikonis and Ríos, 2007;Edwards et al, 2010;Koenig et al, 2018Koenig et al, , 2019 a direct and permanent physical coupling of STIM1 and ORAI1 has been proposed (Edwards et al, 2010;Launikonis et al, 2010) in combination with a nanodomain Ca 2+ depletion within the terminal cisternae of the SR (Koenig et al, 2019) upon opening of the ryanodine receptor during ECcoupling. This notion was supported by respective co-localization of STIM1 and ORAI1 at the triad membranes (Darbellay et al, 2011;Wei-Lapierre et al, 2013;Tammineni et al, 2020), and encouraged by the discovery of a long STIM1 isoform (STIM1L) with supplemental actin binding properties and the ability to form permanent STIM1L/ORAI1-clusters (Darbellay et al, 2011;Saüc et al, 2015). However, others have questioned that idea based on results derived from an (uncalibrated) STIM1/ORAI1 complementation assay (Wei-Lapierre et al, 2013).…”
Section: Physiological Relevancementioning
confidence: 99%